Wissensproduktion, Wissensmobilisierung und Wissenstransfer Chancen und Grenzen der Entwicklung von Wissenschaft und Praxis - Schuster, Johannes; Hugo, Julia; Bremm, Nina; Kolleck, Nina; Zala-Mezö, Enikö (Verlag Barbara Budrich, 2024)
What is the relationship between science and practice? How does research knowledge get into practice? In recent years, there have been increasing calls to examine the relationship between science and practice more closely in order to facilitate a "transfer" of research knowledge into practice. The aim of this volume is to systematise the complex field of the relation between research and practice. The contributions discuss how research and development settings can be designed to establish or increase the relevance of scientific knowledge for practice.